2018
DOI: 10.1016/j.ssmph.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Does mothers' employment affect adolescents' weight and activity levels? Improving our empirical estimates

Abstract: Women’s lives are marked by complex work and family routines — routines that have implications for their children’s health. Prior research suggests a link between mothers' work hours and their children’s weight, but few studies investigate the child health implications of increasingly common work arrangements, such as telecommuting and flexible work schedules. We examine whether changes in mothers’ work arrangements are associated with changes in adolescents’ weight, physical activity, and sedentary behavior u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 87 publications
2
19
1
Order By: Relevance
“…Results from the three studies assessing mental health outcomes and the one study assessing adolescent sedentary health behaviors support the first mechanism. There is a generally consistent pattern in these papers that parental transitions into employment are associated with decreased mental health issues and improved health behaviors while transitions into unemployment are associated with the inverse (Bubonya et al 2017 ; Chase-Lansdale et al 2003 ; Martin et al 2018 ; Moustgaard et al 2018 ). However, there was variation between these studies in which parent’s employment, mother’s or father’s, was significantly associated with child/adolescent mental health.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Results from the three studies assessing mental health outcomes and the one study assessing adolescent sedentary health behaviors support the first mechanism. There is a generally consistent pattern in these papers that parental transitions into employment are associated with decreased mental health issues and improved health behaviors while transitions into unemployment are associated with the inverse (Bubonya et al 2017 ; Chase-Lansdale et al 2003 ; Martin et al 2018 ; Moustgaard et al 2018 ). However, there was variation between these studies in which parent’s employment, mother’s or father’s, was significantly associated with child/adolescent mental health.…”
Section: Discussionmentioning
confidence: 83%
“…Two found that increasing maternal work hours or employment between infancy and childhood/adolescence was associated with increases in child/adolescent BMI (Ettinger et al 2018 ; Jones 2018 ), and one of the two also found paternal employment was associated with decreases in a child’s BMI trajectory (Jones 2018 ). Of the three studies, only one suggested that changes in maternal employment were not associated with overweight/obesity, although this study was restricted to adolescents (Martin et al 2018 ). All three studies were conducted in the U.S.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Self-reported children’s three-days food intake record Negative association was found between maternal working hours and child’s energy, protein and fat intake; breakfast eating Low risk of bias Aniza I et al (2009) (26) Malaysia UMIC Cross sectional study 14 and 16 years (n = 519) Data collected from secondary school students Bivariate analysis and logistic regression Self-reported employment status Self-reported PA using International Physical Activity Questionnaire (IPAQ). Maternal employment had positive association with physical activity Low risk of bias Martin et al, 2018 (27) USA HIC Longitudinal study 12–18 years (n = 10,518) FE and cross-sectional model. Hours a week does s/ he work for pay Self-reported number of times they engaged in various leisure activities during the past week Self-reported weekly hours of watching television, videos and playing video or computer games.…”
Section: Methodsmentioning
confidence: 99%